Optimasi Material Komposit Keramik–Polimer–Serat Alam untuk Peningkatan Efisiensi Energi Serap dan Ketahanan Balistik - Muhammad Kafka Navisa Elzahri; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
The optimization of multilayer ceramic–polymer–natural fiber composite design has become a critical focus in the development of lightweight armor systems with high energy absorption efficiency and enhanced ballistic resistance. Recent studies have highlighted the synergy between ceramic front layers, polymer interlayers, and natural fiber backings that can effectively dissipate impact energy while maintaining optical transparency and structural integrity. This review consolidates 20 recent studies that analyze material selection, layer configuration, and hybridization methods for improving the mechanical and ballistic performance of composite systems. The results indicate that the integration of ceramic strike faces such as alumina (Al₂O₃) or boron carbide (B₄C), coupled with polymer matrices like epoxy or UHMWPE reinforced with natural fibers (kenaf, curaua, jute), yields an optimal balance between lightweight design, high energy absorption, and structural resilience. The review also discusses computational optimization approaches such as finite element modeling (FEM) and analytical hierarchy process (AHP) for predicting multilayer performance.